(untitled) (Praxis Educativa, 2024)
The student groups that face educational transitions, from secondary school to the higher level as well as those that take place within this last school phase, enter into personal, institutional and academic learning processes to achieve affiliation and inhabit new academic spaces. This article proposes, in light of current theoretical-normative contributions, a characterization of the educational transitions experienced by young people, which are divided into two groups, namely: those that occur inter-levels (secondary school - university) and those that take place intra-higher level (university - higher institutes). Based on the recovery of findings located in two recent investigations carried out in the city of Bahía Blanca, province of Buenos Aires, it is proposed to characterize these transitional youth educational passages. For this, the student voices of those who offer us their views on the diversity of contextual, socio-institutional and subjective factors that configured these transitions as bets to continue studying at this last level.